Pendekatan Teknik Relaksasi Terstruktur Untuk Mengurangi Kecemasan Berbahasa Arab di Lingkungan Pesantren - Awalyah, Darmilah; Herdah, Herdah; Darmawati, Darmawati; Kaharuddin, Kaharuddin; Hamsa, Hamsa; Zulkiflih, Zulkiflih (STIQ Amuntai, 2025)
This study investigates the effectiveness of relaxation techniques in reducing Arabic language anxiety among students at the Modern Islamic Boarding School Darul Mahfudz Lekopa’dis. The research aimed to assess (1) the students’ level of anxiety before the intervention, (2) the level of anxiety after the intervention, and (3) the effectiveness of relaxation techniques from a psycholinguistic perspective. A quantitative approach with a quasi-experimental design was employed. Data were collected through observation, interviews, the Arabic Language Anxiety Scale (SKBA), and the Arabic Speaking Proficiency Assessment Rubric (RPKBA). The sample consisted of 46 seventh-grade students divided into an experimental group (n=21) receiving relaxation techniques—breathing dhikr, positive visualization, relaxed role-playing, and staged muhadatsah—and a control group (n=25) undergoing conventional learning. Data were analyzed using paired t-tests and ANCOVA. The results revealed that students’ anxiety levels before the intervention were in the moderate to high range (mean = 113.61). After the intervention, the experimental group showed a significant decrease in anxiety scores from 114.24 to 66.48 (a 42% reduction, t=6.491, p<0.001, Cohen’s d=0.957). Compared to the control group (post-test mean = 110.92), the effect size was huge (Cohen’s d = -4.012), with 85.7% of the experimental group achieving low-anxiety levels. Although the improvement in speaking performance showed a positive trend, it was not statistically significant (p=0.124). From a psycholinguistic viewpoint, reduced anxiety enhanced working memory and facilitated automatic language processing, supporting Krashen’s Affective Filter Hypothesis.